Role of local elites and village level sanitation - Sharmin, Lammia (BRAC Research and Evaluation Division (RED), 2019)
This study aimed to explore the role of local elites and associated factors that prevent or promote sanitation facilities to the poor. The study was conducted in five communities of tive villages of Nilphamari and Lalmonirhat districts. The three communities - Hazipara, Korollabechatari and Moulvipara of Jaldhaka/Nilphamari were selected for the role (active, non-active and newly formed) of Gram Shahayak Committee (GSC -a committee formed by the CFPR-TUP programme comprised of a group oflocal elites to facilitate the ultra poor). The other two communities selected were Babupara from Hatibandha and Balatari from Aditmari of Lalmonirhat district. Babupara was selected as 100 % sanitation community and Balatari as control community. Data were collected through qualitative approaches during February to April 2005. The study shows that all the five communities received local elite's support to some extent. The local elite's support was highest in communities with 100% sanitation and the active GSC. In different communities the factors were different which prevent the adoption of total sanitation. The preventing factors were lack of awareness, lack of land, sanitation as less prioritized issue, and poverty. In these five communities the factors associated with promoting sanitation are elite perception of disease and disease transmission, concept of ideal village with proper sanitation, notion of shame, purdah or just soaber kaj. In most cases the elites were providing help for sanitation through different local institutions. But, it was found that in most of the villages the local institutions were not being able to provide sanitation facility to the poor effectively.